Circadian rhythm of the signal averaged electrocardiogram and its relation to heart rate variability in healthy subjects. Issue 5 (1st May 1998) - Nakagawa, M; Iwao, T; Ishida, S; Yonemochi, H; Fujino, T; Saikawa, T; Ito, M
Abstract : Objective: To examine the circadian variation in the signal averaged electrocardiogram (saECG) and heart rate variability and investigate their relations in healthy subjects. Methods: 24 hour ECGs were obtained with a three channel recorder using bipolar X, Y, and Z leads in 20 healthy subjects. The following variables were determined hourly: heart rate, filtered QRS (f-QRS) duration, low and high frequency components of heart rate variability (LF and HF), and the LF/HF ratio. Results: Heart rate, f-QRS duration, HF, and the LF/HF ratio showed significant circadian rhythms, as determined by the single cosinor method. Heart rate and the LF/HF ratio increased during daytime, and f-QRS duration and HF increased at night. f-QRS duration was negatively correlated with heart rate ( r = 0.95, p < 0.001) and the LF/HF ratio ( r = 0.94, p < 0.001) and positively with HF ( r = 0.93, p < 0.001). Conclusions: f-QRS duration has a significant circadian rhythm in healthy subjects and is closely related to the circadian rhythm of autonomic tone.